Altered Immune Profiles of Natural Killer Cells in Chronic Hepatitis B Patients: A Systematic Review and Meta-Analysis. - Qiong-Fang Zhang; Jian-Ying Shao; Wen-Wei Yin; Yang Xia; Ling Chen; Xing Wang; Huai-Dong Hu; Peng Hu; Hong Ren; Da-Zhi Zhang (PLoS ONE)
Background Natural killer (NK) cells are the main effective component of the innate immune system that responds to chronic hepatitis B (CHB) infection. Although numerous studies have reported the immune profiles of NK cells in CHB patients, they are limited by inconsistent results. Thus, we performed a meta-analysis to characterize reliably the immune profiles of NK cells after CHB infection, specifically frequency, phenotype, and function. Methods A literature search of the computer databases MEDLINE, PUBMED, EMBASE, and Cochrane Center Register of Controlled Trails was performed and 19 studies were selected. The standard mean difference (SMD) and 95% confidence interval (CI) of each continuous variable was estimated with a fixed effects model when I2 < 50% for the test for heterogeneity, or the random effects model otherwise. Publication bias was evaluated using Begg's and Egger's tests. Results The meta-analysis of publications that reported frequency of peripheral NK cells showed that NK cell levels in CHB patients were significantly lower compared with that of healthy controls. A higher frequency of CD56bright NK subsets was found in CHB patients, but the CD56dim NK subsets of CHB patients and healthy controls were similar. CHB patients before and after antiviral therapy with nucleotide analogues (NUCs) showed no statistical difference in NK frequency. The activating receptors were upregulated, whereas inhibitory receptors were comparable in the peripheral NK cells of CHB individuals and healthy controls. NK cells of CHB patients displayed higher cytotoxic potency as evidenced by CD107a protein levels and conserved potency to produce interferon-gamma (IFNγ), compared with their healthy counterparts. Conclusion Our results revealed that CHB patients had a lower frequency of NK cells compared with healthy individuals not treatable with antiviral NUC therapy. With an activating phenotype, NK cells in CHB patients showed better cytotoxic potency and conserved IFNγ production.